Catalytic effect of (H2O)n (n = 1–3) clusters on the HO2 + SO2 → HOSO + 3O2 reaction under tropospheric conditions. Issue 28 (23rd May 2019) - Wang, Rui; Yao, Qiuyue; Wen, Mingjie; Tian, Shaobo; Wang, Yan; Wang, Zhiyin; Yu, Xiaohu; Shao, Xianzhao; Chen, Long
Abstract : The HO2 + SO2 → HOSO + 3 O2 reaction without and with (H2 O) n ( n = 1–3) have been investigated using CCSD(T)/CBS//M06-2X/aug-cc-pVTZ methods, and canonical variational transition state theory with small curvature tunneling. Abstract : The HO2 + SO2 → HOSO + 3 O2 reaction, both without a catalyst and with (H2 O) n ( n = 1–3) as a catalyst, has been investigated using CCSD(T)/CBS//M06-2X/aug-cc-pVTZ methods, and canonical variational transition state theory with small curvature tunneling (CVT/SCT). The calculated results show that H2 O exerts the strongest catalytic role in the hydrogen atom transfer processes of HO2 + SO2 → HOSO + 3 O2 as compared with (H2 O)2 and (H2 O)3 . In the atmosphere at 0 km altitude within the temperature range of 280.0–320.0 K, the reaction with H2 O is dominant, compared with the reaction without a catalyst, with an effective rate constant 2–3 orders of magnitude larger. In addition, at 0 km, it is worth mentioning that the relevance of the HO2 + SO2 → HOSO + 3 O2 reaction with H2 O depends heavily on its ability to compete with the primary loss mechanism of HO2 radicals (such as the HO2 + HO2 and HO2 + NO3 reactions) and SO2 (such as the SO2 + HO reaction). The calculated results show that the HO2 + SO2 → HOSO + 3 O2 reaction with H2 O cannot be neglected in the primary loss mechanism of the HO2 radical and SO2 . The calculated results also show that for the formation of HOSO and 3 O2, the contribution of H2 O decreases from 99.98% to 27.27% with an increase in altitude from 0 km to 15 km, due to the lower relative concentration of water. With the altitude increase, the HO2 + SO2 → HOSO + 3 O2 reaction with H2 O cannot compete with the primary loss mechanism of HO2 radicals. The present results provide new insight into (H2 O) n ( n = 1–3) catalysts, showing that they not only affect energy barriers, but also have an influence on loss mechanisms. The present findings should have broad implications in computational chemistry and atmospheric chemistry.